2021
DOI: 10.1016/j.bja.2021.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neuromuscular block on surgical conditions during short-duration paediatric laparoscopic surgery involving a supraglottic airway

Abstract: Background: Use of an LMA ProSeal™ laryngeal mask airway (P-LMA; Teleflex) with no neuromuscular block is considered a safe alternative to tracheal intubation in short-duration paediatric laparoscopic surgery. However, few studies have evaluated surgical conditions of short-duration paediatric laparoscopic surgery using this anaesthetic technique. We assessed surgical conditions for paediatric laparoscopic inguinal hernia repair using P-LMA with and without neuromuscular block. Methods: Sixty-six patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…Recently, moderate neuromuscular block (TOFc = 1–2) has been reported to improve surgical conditions and reduce the incidence of adverse events in short-duration pediatric laparoscopic surgery with LMA. 28 Whether LMA ventilation and moderate muscle relaxation are suitable for vitreoretinal surgery has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, moderate neuromuscular block (TOFc = 1–2) has been reported to improve surgical conditions and reduce the incidence of adverse events in short-duration pediatric laparoscopic surgery with LMA. 28 Whether LMA ventilation and moderate muscle relaxation are suitable for vitreoretinal surgery has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, deep NMB improves the surgical space during laparoscopic surgery 19 . Our previous study showed that moderate NMB significantly improved conditions for short-duration laparoscopic surgery in children compared with no NMB 2 . However, there are limited data regarding NMB optimising the conditions for laparoscopic surgery in neonates and small infants.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the mean score for the surgical conditions during the laparoscopic surgery reached more than 4 points and the percentage of L-SRS scores of 4 or 5 reached 88% without NMB. The main reason for this result may be immature abdominal wall muscles and weak muscle tension in neonates and small infants 2,20 . Second, the potentiation of NMB and the central neuromuscular effects of volatile anaesthetics may also be an important reason for this result 14,21–23 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations